2022
DOI: 10.1111/ced.15266
|View full text |Cite
|
Sign up to set email alerts
|

A review of the evidence for Mohs micrographic surgery. Part 2: basal cell carcinoma

Abstract: Mohs micrographic surgery (MMS) is considered the gold-standard treatment for basal cell carcinoma (BCC) particularly for sites with a high risk of incomplete excision such as the central face, for tumours with an aggressive growth pattern and consequent unpredictable subclinical extension and for recurrent tumours. However, the process is more time-consuming than for standard excision (SE), and the magnitude of benefit is uncertain. This article aims to provide a more complete picture of current evidence, inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…[11] MMS offers the benefits of minimized incomplete resections and reduced recurrence rates. [22] However, a prospective study on Spanish nonmelanoma skin cancer (NMSC) patients, 92% with BCC, from 2013 to 2020, indicated that 21% of BCC patients treated with MMS faced an elevated risk of a subsequent tumor. [23] Citation analysis, a more robust indicator of article quality and research trends than IF analysis, [24] has highlighted a growing focus on BCC treatments involving the Hh pathway, HPIs, and PDT over the past decade.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[11] MMS offers the benefits of minimized incomplete resections and reduced recurrence rates. [22] However, a prospective study on Spanish nonmelanoma skin cancer (NMSC) patients, 92% with BCC, from 2013 to 2020, indicated that 21% of BCC patients treated with MMS faced an elevated risk of a subsequent tumor. [23] Citation analysis, a more robust indicator of article quality and research trends than IF analysis, [24] has highlighted a growing focus on BCC treatments involving the Hh pathway, HPIs, and PDT over the past decade.…”
Section: Discussionmentioning
confidence: 99%
“…[ 11 ] MMS offers the benefits of minimized incomplete resections and reduced recurrence rates. [ 22 ] However, a prospective study on Spanish nonmelanoma skin cancer (NMSC) patients, 92% with BCC, from 2013 to 2020, indicated that 21% of BCC patients treated with MMS faced an elevated risk of a subsequent tumor. [ 23 ]…”
Section: Discussionmentioning
confidence: 99%
“…46 The cost analysis of MMS for BCC has been reported in our associated review of BCC. 47 The most recently published study was a US study using theoretical modelling based on the data from previously reported studies determined the costeffectiveness of MMS vs. WLE with conventional histopathology for T2a cSCC over 5 years, 45 and concluded that all-in costs per patient (including cost of treating incompletes/recurrences) were US$4365.57 for MMS and US$4699.41 for WLE, making MMS US $333.83 cheaper than WLE. The authors reported that MMS had a 99.9% probability of being more costeffective compared with WLE, and that MMS could cost over three times its current rate and still be more cost-effective than WLE.…”
Section: Cost-effectiveness Of Mohs Micrographic Surgerymentioning
confidence: 99%
“…All other reported studies in this area assessed either keratinocyte cancers jointly or BCC alone 46 . The cost analysis of MMS for BCC has been reported in our associated review of BCC 47 …”
Section: Cost‐effectiveness Of Mohs Micrographic Surgerymentioning
confidence: 99%